Pendidikan Teknologi di Sekolah Inklusi - Indah Mayangsari; Unik Hanifah Salsabila; Tari i; Irva Rani Zulaikha; Fisca Aprita Dewi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2020)
An inclusive school where a school allocates all children without exception to one room regardless of differences in physical, intellectual, social, emotional and other conditional. This includes children with disabilities, children who are lazy to learn, children who are not gifted, street children, who are in the lower class. Inclusive education technology provides a very wide open and friendly space in learning, the inclusive education system always prioritizes mutual respect for differences. Therefore the inclusive educational technology system aims to remove barriers and solve problems and support the implementation of inclusive education for children with special needs. Several adaptive technologies are very important, namely NVDA (Non-Visual Desktop Access), JAWS (Job Access With Speech), I-Chat (I Can hear and talk). This service intends not to differentiate between children from one another, regardless of their background, economy and culture, so that they can develop learning like children in general. improving the success of the goals of inclusive school education.